Vaccination against GnRH as a prelude to surgical castration of horses. (20th January 2021) - Birrell, John R.; Schulman, Martin L.; Botha, Alma E.; Ganswindt, André; Fosgate, Geoffrey T.; Bertschinger, Henk J.
Abstract: Background: Surgical castration is one of the most frequently performed surgeries in horses and is associated with various post‐surgical complications ranging in severity. Objectives: We investigated the effects of administering an anti‐GnRH vaccine to colts for reduction of testis size on the incidence of complications associated with their subsequent surgical castration. Study design: Randomised open controlled trial. Methods: Nineteen colts were randomly assigned to one of the three groups. Treatment Groups V1‐57 and V2‐100 received two treatments of Improvac ® (Zoetis, South Africa) before their castration in the field on either Day 57 or Day 100 following first treatment, respectively. Controls similarly received placebo treatments followed by castration on Day 57. Serial measurements of testicular dimensions and serum samples for measuring serum testosterone concentrations (STCs) and anti‐GnRH antibody titres (ABTs) were obtained pre‐ and post‐vaccination and on the day of castration. Clinical data recorded for 10 days determined post‐surgical complications. Results: All vaccinated colts showed a baseline STC concentration at castration with a strong ABT response. Mean testicular volume of Groups V1‐57 and V2‐100 reduced by 49.7% and 30.8%, respectively, on Day 57 and this further reduced in Group V2‐100 by 63.9% at castration on Day 100. Testis size was significantly correlated with post‐surgical preputial ( P = 0.001) and scrotal ( P = 0.025) swelling. Main limitations: A study population of young light horse breed colts and a relatively small sample size limited this pilot study. Conclusions: Administering two doses of Improvac ® in colts 28 days apart prior to castration effectively reduced their testicular volumes with associated significant post‐surgical improvement in both the incidence and degree of local swelling. These results may inform mitigation of potential post‐surgical complications associated with castration in the field.